** PDF DAMAGE***Hybrid particleboard properties from acacia mangium and 'petal relalang' (leucaena leucocephala) using urea-formaldehyde resin / Mohamad Syazwan Saleh - Saleh, Mohamad Syazwan (Faculty of Applied Sciences, 2015)
ABSTRACT Hybrid particleboard properties from acacia mangium and 'petal belalang' (leucaena leucocephala) using urea-formaldehyde resin.